A Price Formula for Multiple-Commodity Monetary Reserve - Frommer, Joseph C. (Econometrica, 1945)
It has been suggested by several authors' that money be issued against surrender of certain goods and that the issuing agency (we shall call it or simply mint) release these goods against surrender of such money. This money could consist of special certificates, which could circulate in parallel to national currencies without having a fixed exchange rate to them. This would allow experimentation on small scale, without interfering with existing monetary circulation and confining the risk to those who freely consent to accept and use the commodity certificates. It is believed that such commodity certificates could prevent depression and unemployment because if an entrepreneur could pay wages and other expenses with them, then he could continue production even if sale to actual consumers is not warranted: unsold products could be surrendered to the commodity mint. The success of any such scheme depends on the following three factors: 1. An adequate selection of the types of commodities eligible for coinage. These should be durable goods least subject to deterioration and obsolescence. Extension could be made to services such as electric power, etc. It is outside the scope of this paper to make suggestions in this respect. 2. An efficient and inexpensive way to store the commodities. It is believed that the most efficient way would be to leave the commodities against which certificates are being issued (we will call the aggregate of these commodities stock) on the premises of responsible producers, under earmark, the lien on them being released as they are repurchased by him for sale on the free market.2 Such a producer would engage himself to act as an agent of the mint and to surrender such coined goods at coinage prices to holders of commodity certificates. To ensure this, the mint could retain a certain part, say 20 per cent, of the coinage price. When goods were sold, the producer would repay to the mint the part of the coinage price that he had obtained and the balance would remain his. He would be free to sell below coinage price whenever